Elderly care: performance of interventions carried out by More Doctors Program professionals - Maria Elizabeth Gastal Fassa; Elaine Tomasi; Anaclaudia Gastal Fassa; Elaine Thumé; Louriele Wachs; Leonardo Pozza dos Santos; Pamela Volz; Leandro Rodrigues; Luiz Augusto Facchini (Faculdade de Medicina de Botucatu (Unesp), 2019)
ABSTRACT In order to assess coverage and quality of elderly care, a cross-sectional study of 204 interventions of Family Health Specialization students of UFPel was conducted, both connected and not connected to the More Doctors Program (PMM). The coverage difference between the third and first months of intervention and the percentage at the end of the third month were calculated in order to obtain quality indicators. An average increase in coverage of 35.7 percentage points (pp) (32.9, 38.6) was found: 42.1 pp (38.6, 45.7) and 26.1 pp (22.3, 30) were, respectively, related and not related to PMM. Brief Multidimensional Assessment (AMR), up-to-date clinical examination and assessment of the need for dental treatment showed better results in interventions conducted by PMM professionals. The interventions were effective regardless of supply and nationality, obtaining significantly better results those conducted by PMM professionals, especially Cubans.